Usability of a virtual reality manual wheelchair simulator. - Chaar, Fadi; Archambault, Philippe S. (Disability & Rehabilitation: Assistive Technology, 2023)
Individuals with impaired mobility often require assistance for getting around. The skilled use of a manual wheelchair (MW) is required in order to gain independence while preventing injuries. Training in a virtual reality (VR) setting allows for safe practice of MW skills in a wide range of environments. We developed a low-cost MW simulator which includes visual and haptic feedback. Our objectives were to assess the usability and fidelity of the VR simulator, by clinicians and expert MW users, and to determine whether the addition of haptic feedback would positively improve the user's experience. This mixed method study investigated the sense of presence, overall experience and ease of use of the experience in six MW users, as well as five clinicians (wheeled mobility experts) who practiced in the simulator. Participants reported a positive perception of usefulness, sense of presence, and immersion during the MiWe simulator experience. The addition of haptic feedback to the simulator significantly enhanced fidelity of the overall experience, compared to the no-feedback condition. Our low-cost simulator was well perceived by clinicians and MW users and was considered as a potentially useful tool to complement MW skill training. We developed a low-cost, virtual reality simulator with visual and haptic feedback, for the practice of manual wheelchair skills. Expert clinicians and wheelchair users reported a positive experience after practicing in the wheelchair simulator, in terms of presence, realism and usability. Participants highlighted the potential usefulness of our low-cost simulator in the training of manual wheelchair skills.